2020
DOI: 10.1177/2632077020942959
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Brief, Bystander Bullying Prevention Program on Depressive Symptoms and Passive Suicidal Ideation: A Program Evaluation Model for School Personnel

Abstract: The purpose of this article is to present a study that can serve as a model of program evaluation for school personnel that can be used to improve services and demonstrate program efficacy to key stakeholders. The study presented in this article evaluated the impact of a brief, bystander bullying program (“stealing the show,” “turning it over,” “accompanying others,” and “coaching compassion,” [STAC]) on depressive symptoms and passive suicidal ideation among middle school students in a rural, low-income commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Research evaluating school‐wide bullying prevention programs that include bystander intervention has demonstrated that these programs are effective in reducing cyberbullying (Williford et al, 2013), as well as reducing depression and anxiety among students trained in the program (Williford et al, 2012). Similarly, research indicates stand‐alone bystander interventions are also effective in reducing depression and anxiety for students trained to intervene in bullying situations (Doumas et al, 2019; Midgett & Doumas, 2019b; Midgett et al, 2017; Midgett, Doumas, Peralta, et al, 2020). Therefore, implementing school‐based programs that include a bystander component (e.g., KiVA; Salmivalli et al, 2011) or stand‐alone bullying bystander interventions (e.g., STAC, Midgett et al, 2015) may be promising approaches for reducing the mental health risks associated with witnessing cyberbullying.…”
Section: Discussionmentioning
confidence: 99%
“…Research evaluating school‐wide bullying prevention programs that include bystander intervention has demonstrated that these programs are effective in reducing cyberbullying (Williford et al, 2013), as well as reducing depression and anxiety among students trained in the program (Williford et al, 2012). Similarly, research indicates stand‐alone bystander interventions are also effective in reducing depression and anxiety for students trained to intervene in bullying situations (Doumas et al, 2019; Midgett & Doumas, 2019b; Midgett et al, 2017; Midgett, Doumas, Peralta, et al, 2020). Therefore, implementing school‐based programs that include a bystander component (e.g., KiVA; Salmivalli et al, 2011) or stand‐alone bullying bystander interventions (e.g., STAC, Midgett et al, 2015) may be promising approaches for reducing the mental health risks associated with witnessing cyberbullying.…”
Section: Discussionmentioning
confidence: 99%
“…The plethora of research on the subject [ 2 ], however, has focused mainly on the dyadic interplay between bullies and victims [ 3 , 4 ]. As bullying rarely occurs without others observing it, a comprehensive viewpoint for the study of bullying should include bystanders, who are the largest group impacted by bullying, by either directly observing acts of bullying or by being exposed to bullying mediated by technology [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to the study of bystanders of bullying considers bystanders as victims by proxy. This line of research has focused on how witnessing bullying acts impacts the well-being and psychological health of bystanders [ 7 ]. It has demonstrated a correlation between witnessing an act of bullying and suicide ideation [ 8 ], symptoms of depression among bystanders [ 9 , 10 , 11 ], especially among those who were exposed to bullying [ 12 ], repression of empathy of bystanders [ 13 ], and increased feelings of guilt [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations